Seeds and seedlings of Brassica - Cory, Victor L. (My University, 1904)
Introduction: Object of Investigation.- The cabbage plant, Brassica oleracea, presents us with a wider range of varieties than perhaps any other cultivated plant. There is no other of our garden vegetables which gives so many useful forms as it does. In the wild state it is found on the coasts of western Europe, and persons familiar only with the garden forms would, most likely, not recognize it. Seedlings of the wild plant grown in rich soil show great variations. Selection of these variations has resulted in a number of races, each with numerous varieties. At maturity these races differ very markedly in certain characters. It is not difficult to appreciate the difference between the green and the red cabbage with great single heads; Brussel-sprouts with numerous little heads; broccolis and cauliflowers with the greater number of their flowers in an aborted condition, incapable of producing seed and borne in a dense corymb instead of in an open panicle; Savoys with their blistered and wrinkled leaves; and borecoles and kales which come nearest to the wild parent form. Now the seeds of these races are uniform to a degree. Seen in mass some are a little lighter or darker, some are smaller or larger than usual, but in no case are there any distinguishable markings. As there are no distinguishable features in the seeds, the question we are concerned with is: How soon in the life history of the plants does differentiation begin.
Seeds and seedlings of Brassica, with especial reference to B. Cleracea and B. Naous
Citation: Cory, Victor L. Seeds and seedlings of Brassica. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Seeds; Plant Types; Horticulture; Theses